Nano High‐Entropy Materials: Synthesis Strategies and Catalytic Applications. Issue 2 (27th September 2020) - Li, Huining; Zhu, Han; Zhang, Songge; Zhang, Ning; Du, Mingliang; Chai, Yang
Abstract : The multicomponent combinations of metals in nanoscale high‐entropy materials (HEMs) have unique structure and physical and chemical properties, which provide them tailorable active sites and catalytic performance and attract intensive researches in recent years. Herein, an overview of the development of the synthesis strategies for various types of HEMs and their formation mechanisms is provided. These synthesis methods are compared, and their advantages and challenges are illustrated. The superior catalytic behavior of HEMs compared with their traditional analogue materials in heterogeneous catalysis are discussed and the underlying structure–activity correlation is revealed. The perspectives for future HEMs design are provided to achieve significant progress for catalytic applications. Abstract : Recent progress in the synthesis strategies and catalytic performance of nanoscale high‐entropy materials (HEMs) are summarized herein. Their formation mechanisms and structure–activity correlations are presented for the sake of facilitating the future design and applications of HEMs nanostructure. The challenges and perspectives in this field are also summarized.